(untitled) (The Journal of Cultural Perspectives, 2025)
The study aims to deal with the playwrights’ purpose behind adopting and adapting historical subject matter to revisit, define, redefine, deconstruct, challenge, and reconstruct the history, culture, and past narratives. Moreover, the study’s objective is to examine playwrights’ purpose to address contemporary cultural issues by dealing with historical stories. For instance, Shahid Nadeem’s Dara and Karnad’s The Dreams of Tipu Sultan challenge the prevalent narratives of the past. Nadeem deconstructs the past portrayal of Dara Shikoh as a villain in Pakistani history. He maintains his argument by unearthing Dara’s poetic, philosophical, and humanistic nature, where he tries to attain inter-religious harmony. On the other hand, Karnad exposes the misrepresentation and mishandling of Tipu Sultan’s historical image by English historians and novelists in history. The reason behind the distortion was the victorious and rebellious nature of Tipu, who defeated the East India Company in wars and kept on challenging their authority until his death. The playwright reconstructs the past by highlighting Tipu’s political, social, and economic skills to make his country great under his sovereign state.